Antisene Approaches of Tobacco and Potato ADP-Glucose Pyrophosphorylase (AGPase) Under TA29 and NTM19 Promoter in Tobacco Plants - Mamun, ANK (Bangladesh Journal of Genetics and Biotechnology, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Key words: Tobacco; potato; ADP-glucose pyrophosphorylase; TA29 and NTM19 promoter Bangladesh j. genet. biotechnol. 7(1&2): 43-48 2006 (June & December)